전투무선망에서 신뢰성있는 멀티캐스트 MAC 프로토콜 - Jeong hun Kim (The Graduate School, Ajou University, 2012)
Combat net radio (CNR) networks are the most important communication infra for the ground forces such as infantry of Army and Marine corps. CNR is the primary means for short-range (less than 35 kilometers (22miles)) secure voice command and control (C2) below division level. It is also the secondary means for combat support (CS) and combat service support (CSS) units throughout the corps. Historically, mobile ad hoc network was originally introduced for this CNR networks. Mobile ad hoc networks have been used for tactical networks such as CNR to improve battlefield communications and survivability. The lack of infrastructure and the peer-to-peer nature of ad hoc networking make random access protocols the natural choice for medium access control in ad hoc networks. Indeed, most proposals of MAC protocols for ad hoc networks are based on the random access paradigm; in addition, the CSMA/CA scheme was selected by the IEEE802.11 committee as the basis for its standards due to the inherent flexibility of this scheme [1]. Therefore, the IEEE 802.11 standards are the most potential candidate for CNR networks in commercial area. MIL-STD-188-220 is the Interoperability Standard for Digital Message Transfer Device (DMTD) Subsystems of American Department of Defense. This standard has been widely used in data communication among command, control, communications computer and intelligence (C4I) systems [3-5]. The physical, datalink and network layers of OSI-7-layers are handled in MIL-STD-188-220. The commercial protocols are used for the higher layers. The data-link layer is the largest part of the protocol. The MAC protocol of MIL-STD-188-220 is implemented by 6 different network access delay (NAD) mechanisms. Among the 6 NAD schemes, R (random) - NAD and DAP (deterministic adaptable priority) - NAD are mandatory. R-NAD provides all stations with an equal opportunity to access the network, which increases the possibility of collisions like CSMA/CA used in IEEE 802.11 standards. Multicasting is an efficient communication service for supporting multi-point applications in the Internet. In tactical networks, the role of multicast services is potentially even more important due the bandwidth and energy savings that can be achieved through multicast packet delivery [2]. IEEE 802.11 standards and MIL-STD-188-220 also specify multicast services as well as unicast services in Layer 2. Military communication systems generally require reliability with the corresponding ACKs at multiple levels. However, the conventional multicast schemes over IEEE 802.11 and MIL-STD-188-220 have some constraints in respect to time overhead. Since ACK packet receptions from all multiple receivers degrade the channel efficiency and reduce the overall network performance. This degradation is worsened as the number of multicast receivers increases. Throughout this thesis, we investigate the characteristics of tactical multicast services in Layer 2, and then we propose reliable multicast MAC protocols for the candidate commercial and military standards. We select the IEEE 802.11 standard for the commercial standard and MIL-STD-188-220 for the military standard.
학위논문(박사)아주대학교 일반대학원 :NCW학과,2012. 2
Keywords: 전투무선망; 멀티캐스트; MAC